Translational health research: perspectives from health education specialists - Holly J Mata; Sharon Davis (Clinical and Translational Medicine, 2012)
Abstract The phrase “from bench to bedside to curbside” is a common definition of translational research among health disparities researchers. Health Education Specialists can make important contributions to the field of clinical translational medicine, particularly in light of U.S. health care reform and a renewed emphasis on medical home or health care home models. Health Education Specialists have the training and experience to engage in and facilitate translational research, as well as the opportunity to learn from the translational efforts of other professions and enhance our research, practice, and community partnerships through translational efforts. In this paper, a Translational Health Education Research framework for health education researchers is suggested to foster increased translational efforts within our profession as well as to promote interdisciplinary collaborations to translate a variety of health‐related research. A conceptual framework adapted from translational health disparities research that highlights the level and scope of translational research necessary for changes in practice and policy is also provided.